Comprehensive Evaluation of the Antibacterial and Antifungal Activities of Carlina acaulis L. Essential Oil and Its Nanoemulsion - Antonio Rosato; Alexia Barbarossa; Ahmed M. Mustafa; Giulia Bonacucina; Diego Romano Perinelli; Riccardo Petrelli; Filippo Maggi; Eleonora Spinozzi (MDPI AG, 2021)
Plants are considered to be an excellent source of new compounds with antibiotic activity. Carlina acaulis L. is a medicinal plant whose essential oil (EO) is mainly characterized by the polyacetylene carlina oxide, which has antimicrobial properties. The aim of this study was to evaluate the antimicrobial and antifungal activities of C. acaulis EO, carlina oxide, and nanoemulsion (NE) containing the EO. The EO was obtained through plant roots hydrodistillation, and carlina oxide was purified from it through silica gel column chromatography. The NE containing C. acaulis EO was prepared with the high-pressure homogenization method, and the minimum inhibitory concentration (MIC) was determined against several bacterial and fungal strains for all the C. acaulis-derived products. The latter resulted active versus all the screened Gram-positive bacterial strains and also on all the fungal strains with low MIC values. For yeast, the EO and carlina oxide showed good MIC values. The EO-NE demonstrated a better activity than the pure EO on all the tested bacterial and fungal strains. The results suggest that C. acaulis-derived products could be potential candidates for the development of natural antibacterial and antifungal agents.